2009
DOI: 10.1080/01421590802516723
|View full text |Cite
|
Sign up to set email alerts
|

Resident run journal club: A model based on the adult learning theory

Abstract: Background: Multiple formats of journal club exist but data is lacking regarding which model is most effective. Many residents are dissatisfied with their current format, which was the case at our institution. Aim: This article discusses a resident run model, residents' perceptions following its implementation, and recommendations for running a successful journal club. Methods: A resident run model of journal club was developed based on Adult Learning Theory. A 30-question survey was created to assess resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 16 publications
1
50
0
Order By: Relevance
“…Clinicians may feel they are attending a statistical meeting rather than a continuing medical education event. It is the organizers' responsibility to improve participant satisfaction; however, there are very few published strategies to turn to (7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians may feel they are attending a statistical meeting rather than a continuing medical education event. It is the organizers' responsibility to improve participant satisfaction; however, there are very few published strategies to turn to (7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their common implementation, journal clubs are often unsatisfactory for both the staff physicians and residents (7,8). Thus, journal club organizers are often left with the challenge of improving club design and execution (9,10) -a difficult task given the relative paucity of published information in this area.…”
mentioning
confidence: 99%
“…Although the situation is not entirely parallel, 2 studies of medical residents' journal clubs found that attendees favored having the meetings run by the residents, without faculty participation. 9,11 Other factors that have been reported to improve the quality and/or participation in healthcare journal clubs include involving a medical librarian to facilitate article selection and other aspects of the process. 13 On-line journal clubs 10 and the incorporation of video conferencing into the meeting environment 14 have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,10 Several authors have attempted to identify aspects of journal club structure and operation that best facilitate attendance and satisfaction, 2,3,11,12 including designating a club leader, clearly defined goals, Internet marketing the club, and making the papers available to the participants beforehand. 2,3 Several other aspects of journal club operation have also been touted as promoting participation, although the findings and recommendations of various authors have differed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation